2021
DOI: 10.3928/24748307-20210911-01
|View full text |Cite
|
Sign up to set email alerts
|

Using Feasibility Data and Codesign to Refine a Group-Based Health Literacy Intervention for New Parents

Abstract: Few health literacy interventions exist for new parents. We developed a group-based health literacy program (“Parenting Plus”), which was initially tested in a feasibility study in 2018. In this brief report, we describe how feasibility findings were incorporated into the Parenting Plus program. Using a codesign process with patient partners (feasibility study participants) and health staff to revise the program, version 2 was tested in a single-site pilot using pre- and post-intervention testing. Parents olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Evolving capability of researchers and health staff was achieved through the secondment process which enabled health staff and researchers to work directly together on the Parenting Plus project over a 10-month period. 40 Formal and informal interactions between team members during this time helped us to appreciate one another's worldviews, priorities and ways of working. Health staff were also involved in research capacity building and transferable skills training in data collection and analysis.…”
Section: Evolving Capability and Understandingmentioning
confidence: 99%
“…Evolving capability of researchers and health staff was achieved through the secondment process which enabled health staff and researchers to work directly together on the Parenting Plus project over a 10-month period. 40 Formal and informal interactions between team members during this time helped us to appreciate one another's worldviews, priorities and ways of working. Health staff were also involved in research capacity building and transferable skills training in data collection and analysis.…”
Section: Evolving Capability and Understandingmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] This type of plan is well suited to online formats 14,[22][23][24] which allows for easy distribution, scale-up, adaptation to different contexts and inclusion with other online resources such as decision aids or patient education. [25][26][27] Recent research indicates they may be a particularly useful action plan format for groups with varying health literacy levels. 13,26 Despite the evidence-base underpinning implementation intentions and volitional help sheets, there is little qualitative research to T A B L E 1 Factors which INCREASE the effectiveness of implementation intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Volitional help sheets have demonstrated effectiveness across a range of behaviours, including healthy eating, increasing physical activity and smoking cessation 15–21 . This type of plan is well suited to online formats 14,22–24 which allows for easy distribution, scale‐up, adaptation to different contexts and inclusion with other online resources such as decision aids or patient education 25–27 . Recent research indicates they may be a particularly useful action plan format for groups with varying health literacy levels 13,26 …”
Section: Introductionmentioning
confidence: 99%
“…Since I obtained my doctoral degree, my work in health literacy has moved out of the adult education sphere and more toward health systems, where I have adapted the original adult education program for different community and clinical populations, including adults living with chronic kidney disease ( Muscat, Lambert, et al, 2021 ) and new parents ( Muscat, Ayre, et al, 2021 ). This process has made me appreciate—possibly more than ever—Dr.…”
mentioning
confidence: 99%
“…These include, for example, skills related to health system vocabulary, dialogue, and discussion with health providers ( Rudd, 2002 ), and increasingly in critical appraisal of health information. Our own work has shown that embedding skills within health topics of interest may be an opportune way to achieve this in health systems where health literacy programs “compete” in an already crowded space of health communication and information transfer ( Muscat, Ayre, et al, 2021 ; Zwi et al, 2022 ).…”
mentioning
confidence: 99%